Piast Burials Abroad as an Example of the Migration of Slavic Rulers in the Middle Ages and Early Modern Era - Mądry, Wojciech (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
The article presents a few relatively little-known burials of male representatives of the Piast dynasty located outside the present-day borders of Poland, which were recognized unambiguously by researchers as Slavic. These burials are evidence of Piasts’ travels around the world for various purposes and in various circumstances. The author identifies four types of circumstances leading to Piasts’ being put to rest away from their homeland and assigns specific representatives of this dynasty to each type. The article also emphasizes the fact that Piast princesses were often married off to foreign rulers away from their family home. The monument called the Column of Tears in the village of Ulesie near Legnica is a symbol of this practice. By drawing attention to the Piast dynasty burial sites in various parts of Europe, the article aims to stimulate a broader view on the contribution of the representatives of the Piast dynasty to the political life of Europe in the Middle Ages and at the beginning of the modern era.